Rapid prototyping models for dysplastic hip surgeries in Malaysia - Dhakshyani, R.; Nukman, Y.; Abu Osman, Noor Azuan (2012)
This research was done to determine the benefits of fused deposition modelling (FDM) models produced from computed tomography (CT) data in dysplastic hip surgeries. Since there is limited published information on the benefits of FDM models in dysplastic hip surgeries, this questionnaire study was conducted to provide such information. MIMICS software was used to prepare the three-dimensional model of the patients which was then used to produce the FDM models. These models were given to the orthopaedic surgeons with a questionnaire to obtain their feedback. Orthopaedic surgeons found the FDM models very useful in planning surgery which helped them make decisions and increased their skill and knowledge. The orthopaedic surgeons found that the models were excellent as surgical visual aid, helpful in preplanning surgery and determining surgery procedure. The results obtained showed the benefit of using FDM models in dysplastic hip surgeries.